Assessment of Human Factors After Advanced Life Support Courses Comparing Simulated Team and Real Team Assessment: A Randomized Controlled Cohort Trial - Nabecker, Sabine; Huwendiek, Sören; Seidl, Christian; Hana, Anisa; Theiler, Lorenz; Greif, Robert (Frontiers in Cardiovascular Medicine, 2022)
Aim of the study: Human factors are essential for high-quality resuscitation team collaboration and are therefore taught in international advanced life support courses, but their assessment differs widely. In Europe the summative life support course assessment tests mainly adherence to guidelines but little human factors. This randomized controlled simulation trial investigated instructors’ and course participants’ perception of human factors assessment after two different summative assessments. Methods: All fifth/sixth-year medical students who attended 19 advanced life support courses according to the 2015 European Resuscitation Council guidelines during one study year were invited to participate. Each course was randomized to either: 1) Simulated team assessment (one instructor simulates a team, the assessed person leads this “team” through a cardiac-arrest scenario test); 2) Real team assessment (4 students form a team, one of them is assessed as the team leader; team members are not assessed and act only on team leader’s commands). After the summative assessments, instructors, and students rated the tests’ ability to assess human factors using a visual analogue scale (VAS, 0=no agreement, 10=total agreement). Results: 227 students participated in the 1-day Immediate Life Support courses, 196 students in the 2-day Advanced Life Support courses, additionally 54 instructors were included. Instructors judged all human factors significantly better in real team assessments; students rated leadership and situational awareness comparable between both assessments. Assessment pass rates were comparable between groups. Conclusion: Summative assessment in real teams was perceived significantly better to assess human factors. These results might influence current summative assessment practices in advanced life support courses. Conclusion: Summative assessment in real teams was perceived significantly better to assess human factors. These results might influence current summative assessment practices in advanced life support courses.